Shari'a in Sydney and New York A Perspective from Professionals and Leaders Dealing with Islamic Law - Possamai, Adam; Dagistanli, Selda; Turner, Bryan S. 1945-; Voyce, Malcolm (2019)
This article explores how Shari'a is conceptualized and experienced by 50 Muslim legal professionals and leaders in Sydney and New York. It analyses qualitative data on issues concerning the experience of Muslims with Shari'a, on how this can be improved in both countries and on how compatible Shari'a is with their respective legal systems. While the Muslim community should not be homogenized in either of these two global cities, the analysis discovers strong similarities with regard to dealing with a parallel legal system and implementing a more formal process. The New York sample expresses stronger support for a more community-based approach, while the focus on Shari'a compliant business is stronger among the Australian participants. With regard to gender issues, the large majority of the respondents offer a strong reflective approach to dealing with these issues.
Keywords: Islam; Shari'a; legal professional; Sociology